2011
DOI: 10.1007/s00330-011-2331-z
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of semi-quantitative multiphase dynamic contrast-enhanced MRI as a predictor of malignancy in complex adnexal masses: radiological and pathological correlation

Abstract: Semi-quantitative DCE-MRI threshold criteria are effective for predicting ovarian malignancy. The surgical approach may be altered depending on DCE-MRI threshold criteria analysis. Borderline tumours demonstrate significant overlap with benign lesions using DCE-MRI threshold criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
55
3
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 24 publications
10
55
3
4
Order By: Relevance
“…In theory, the EA was higher in malignant than in borderline tumors and higher in borderline tumors than in benign tumors, which was confirmed by several studies [9, 10, 13, 14]. However, our study showed that the mean EA of malignant tumors was slightly lower than in borderline tumors and higher than in benign tumors (267.4 ± 86.2 vs. 269.3 ± 70.0 and 220.2 ± 90.5) ( P  > 0.05), which was not in accordance with previous studies [9, 10, 13, 14]. Therefore, further work needs to be done to verify our present findings.…”
Section: Discussionsupporting
confidence: 66%
“…In theory, the EA was higher in malignant than in borderline tumors and higher in borderline tumors than in benign tumors, which was confirmed by several studies [9, 10, 13, 14]. However, our study showed that the mean EA of malignant tumors was slightly lower than in borderline tumors and higher than in benign tumors (267.4 ± 86.2 vs. 269.3 ± 70.0 and 220.2 ± 90.5) ( P  > 0.05), which was not in accordance with previous studies [9, 10, 13, 14]. Therefore, further work needs to be done to verify our present findings.…”
Section: Discussionsupporting
confidence: 66%
“…58 of these lesions were previously published at our institute (St Bartholomew's Hospital, London, UK), but their myometrium was not assessed. 2 The age range was 19-75 years with a mean age of 50.5 years. The size of the lesions ranged from 2 to 28 cm.…”
Section: Resultsmentioning
confidence: 99%
“…Time-intensity curves and descriptive DCE parameters of their enhancing solid components have aided differentiation of benign from borderline/ malignant lesions. [1][2][3][4][5][6] However, semi-quantitative assessment of DCE, which is based on signal enhancement, is altered by cardiac flow rate, arterial blood pressure and contrast agent dose. To overcome this, internal references have been suggested to provide lesion-to-internal (lesion-internal reference) ratios.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Dinamik kontrastlı MRG'de; malign over kitlelerinin (60. sn'de) benign lezyonlardan daha çok kontrast tuttuğu ve %91 doğruluk değeri olduğu gösterilmiştir [20]. Diğer bir teknikte zaman-intensite eğrilerine göre; tip 1, pik olmadan tedrici artış (benign), tip 2, önce erken kontrast tutulumu ve takiben plato (borderline-sınır tümörler), tip 3 myometriuma göre hızlı, erken kontrast tutulumu ve takiben 'washout', (invaziv over tümörleri) için tipik bulunmuştur [21].…”
unclassified